Brown coal char CO2-gasification kinetics with respect to the char structure. Part I: Char structure development. (15th July 2015) - Komarova, Evgeniia; Guhl, Stefan; Meyer, Bernd
Highlights: Brown coal char gasification in a fluidized-bed reactor. Investigations on char structure development. Char structure analysis and measurements techniques. Abstract: German lusatian brown coal was gasified in a laboratory scale fluidized-bed type reactor using CO2 as gasification agent. The experiments were carried out at temperatures of 800, 850, 900 and 950 °C. The raw brown coal was first pyrolyzed in a way to minimize the volatile matter content in the resulting char. Then the char was used to study the Boudouard reaction (C + CO2  = 2CO) with respect to the char structure. Temperature range as well as char particle size fraction (200–315 μm) were specifically chosen in order to approach the chemically controlled kinetic regime. Chars were gasified completely as well as partially up to certain carbon conversion degrees. Structure characteristics of partially gasified chars such as surface area and porosity were determined using the N2 adsorption technique and mercury porosimetry respectively. Surface area values were obtained from adsorption isotherms using several methods: Brunauer–Emmett–Teller (BET), Langmuir, t-plot and Barrett–Joyner–Halenda (BJH). The choice of the methods was discussed. The results show that the development of char surface area with char conversion at lower temperature (800 °C) slightly differs from those at higher temperatures (850–950 °C). It was found, that the heterogeneous char-CO2 reaction mostly takes place on mesopore surface area, which presumably is developed from micropore surface area in the beginning of char conversion. This was also confirmed by mercury porosimetry analysis. Total char porosity increases linearly during char conversion at all studied temperatures. The change of char particle size during carbon conversion showed no obvious change in char particle size until 50% of carbon conversion; however, the size decreased beyond this carbon conversion from particle fragmentation.